The open and closed space in the poetry of Ibn Khafajah al-Andalusi: Study in selected models - Omer, Nasreen; Hussain, Mohammed (Humanities Journal of University of Zakho, 2021)
Humans realized the role that the place plays in his life, in the past and in the present, as the idea of place was rooted in human thought and flourished with the development of human thought in dealing with the outside world surrounding it. As the presence of the place in the Arabic poem is rooted since the pre-Islamic era until the present day, and we see a distinct presence of it in the Andalusian poem due to the enjoyment of that country with beauty and splendor, especially with the poet Ibn Khafajah, who is the focus of our research and who was able to give the place dimensions other than the distance Geographical and engineering, rather dimensions that emit many connotations, suggestions and symbols to reveal aesthetically, decipher the rest and analyze them as the outlet takes him to express his psychological state and the feelings of joy or sadness that arise in it, so he interacts with those places and even merges with them to the extent that he diagnoses them, interrogates them and gives them human qualities.This research aspires to artistically recall the open and closed space in Ibn Khafajah’s poetry and the role of these places in the poet’s life and the impact they leave on him, such as his feeling of joy and happiness in the open space, and his feeling of sadness and despair in the closed place. Among his open spatial symbols (the country of Andalusia, the councils of fun and the mountain, the moon, the rising of dawn) and among his closed spatial symbols: (the place of alienation, the house, the grave, as he examined, analyzed and manipulated it in his poetic language, enriching it semantic and aesthetically, with a lot of use of the element of imagination that helped him to evoke The place and the hair was decorated with luster and beauty.